2004
DOI: 10.1142/s0219581x04001778
|View full text |Cite
|
Sign up to set email alerts
|

MODIFICATION OF GROWTH MODE OF Ge ON Si BY PULSED LOW-ENERGY ION-BEAM IRRADIATION

Abstract: Scanning tunneling microscopy (STM) and reflection high-energy electron diffraction (RHEED) experiments were performed to study growth modes induced by hyperthermal Ge + ion action during molecular beam epitaxy (MBE) of Ge on Si(100). The continuous and pulsed ion beams were used. These studies have shown that ion-beam bombardment during heteroepitaxy leads to decrease in critical film thickness for transition from twodimensional (2D) to three-dimensional (3D) growth modes, enhancement of 3D island density and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…For Ge/ Si͑001͒ QD's, several approaches have been exploited to tune the uniformity of the Ge island sizes and shapes, such as manipulating the substrate temperature 8,9 and the deposition sequence, 10 vertical ordering in QD multilayers, [11][12][13] surfactant-mediated growth, 14,15 deposition on vicinal, 16 and oxidized 17 surfaces, ion-beam stimulated growth. 18 Despite some technological progress any information on how these approaches affect the energy spectrum of carriers confined in an ensemble of QD's is still missing. In this work we suggest an alternative way to improve the homogeneity of Ge/ Si QD's sizes and present the unambiguous evidence that this approach certainly allows to reduce dispersion of hole energy levels in the dots.…”
Section: Introductionmentioning
confidence: 99%
“…For Ge/ Si͑001͒ QD's, several approaches have been exploited to tune the uniformity of the Ge island sizes and shapes, such as manipulating the substrate temperature 8,9 and the deposition sequence, 10 vertical ordering in QD multilayers, [11][12][13] surfactant-mediated growth, 14,15 deposition on vicinal, 16 and oxidized 17 surfaces, ion-beam stimulated growth. 18 Despite some technological progress any information on how these approaches affect the energy spectrum of carriers confined in an ensemble of QD's is still missing. In this work we suggest an alternative way to improve the homogeneity of Ge/ Si QD's sizes and present the unambiguous evidence that this approach certainly allows to reduce dispersion of hole energy levels in the dots.…”
Section: Introductionmentioning
confidence: 99%
“…As it has been mentioned, several approaches have been exploited to tune the morphology and structural properties of Ge QDs, such as manipulating the Ge growth 43 and overgrowth 44 temperatures, the Ge coverage, 45 vertical ordering in QD multilayers, [46][47][48] surfactant-mediated growth, 49 50 deposition on vicinal 51 and oxidized 52 surfaces, ion-beam stimulated growth. 53 Another parameter which can control the formation of QDs through the kinetic factors is the dot deposition rate R. Little work has been done on the influence of grown rate on the formation of Ge/Si(001) nanoclusters. Recently, Cho et al 54 demonstrated the effect of deposition rate on the spatial distribution of dome-shaped Ge islands fabricated at high (600 C) temperature.…”
Section: Effect Of Growth Rate On Germanium Hut Clustersmentioning
confidence: 99%
“…A detailed knowledge of the Si surface structure which is formed in the above conditions-its reconstruction, defectiveness, fine structural peculiarities, etc.-is of great importance too because this structure may affect the properties of nanostructured layers deposited on it. For instance, the Si surface structure may affect the magnitude and the distribution of the surface stress of the Ge wetting layer on nanometer scale when the Ge/Si structure is grown, which in turn affect the Ge nanocluster nucleation and eventually the properties of quantum dot arrays formed on the surface [1,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%